Diagnosis of human granulocytic anaplasmosis in Belgium by combining molecular and serological methods. Issue 6 (9th October 2014) - Hing, M.; Woestyn, S.; Van Bosterhaut, B.; Desbonnet, Y.; Heyman, P.; Cochez, C.; Silaghi, C.; Sprong, H.; Fournier, P. E.; Raoult, D.; Neirinckx, P.; Heuninckx, W.
Abstract We report here one new, hospitalized case of Anaplasma phagocytophilum in Belgium. The clinical presentation of anaplasmosis, its treatment and the molecular and serological relevant laboratory methods are briefly developed.